70.6k views
2 votes
Simplify: 12(2 + 2 3 x) A) 24 + 2 3 x B) 24 + 8 3 x C) 24 + 4x D) 24 + 8x

User Yulanda
by
5.5k points

1 Answer

3 votes

Option D

The simplified form of given expression is
12(2+(2)/(3)x) = 24 + 8x

Solution:

Given that we have to simplify:


12(2+(2)/(3)x)

Let us simplify the given expression


\rightarrow 12(2+(2)/(3)x)

Multiply the constant outside the bracket with each term inside the bracket


\rightarrow 24 + 12 * (2x)/(3)

Simplify the above expression


\rightarrow 24 + (4 * 2x)

Solve for brackets. Multiply the terms inside the bracket


\rightarrow 24 + 8x


12(2+(2)/(3)x) = 24 + 8x

Thus Option D is correct

User Fals
by
4.4k points